Institutional Ownership Effect on Company Values with CSR and DER as An Intervening Variable - Dea Ariana; Fauji Sanusi; Wawan Ichwanudin (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to examine whether institutional ownership has an effect on firm value with debt policies and corporate social responsibility as intervening variables in automotive sub-sector manufacturing companies and their components listed on the Indonesia Stock Exchange for the 2015-2021 period. In this study, institutional ownership is measured by INST, firm value is measured by price to book value (PBV), debt policy is measured by debt to equity ratio, corporate social responsibility is measured by CSRDI index. The population used in this study is the automotive sub-sector manufacturing companies and their components listed on the Indonesia Stock Exchange for the 2015-2021 period. The sample of this study amounted to 12 companies from a total population of 84 companies. Sampling using purposive sampling method. The data analysis tool used in this research is path analysis using smartpls3 software. The results of this study indicate that: (1) Institutional ownership has a significant positive effect on debt policy. (2) Institutional ownership has no significant positive effect on corporate social responsibility. (3) Institutional ownership has no significant positive effect on firm value. (4) Debt policy has a significant negative effect on firm value. (5) Corporate social responsibility has a significant positive effect on firm value. (6) Debt policy cannot mediate institutional ownership on firm value. (7) Corporate social responsibility cannot mediate institutional ownership on firm value.